An investigation of ribosomal protein L10 gene in autism spectrum disorders - Rastam Maria; Anckarsäter Henrik; Nygren Gudrun; Goubran-Botros Hany; Betancur Catalina; Chaste Pauline; Durand Christelle M; Fauchereau Fabien; Delorme Richard; Gong Xiaohong; Gillberg I Carina; Kopp Svenny; et al. (BMC, 2009)
Abstract Background Autism spectrum disorders (ASD) are severe neurodevelopmental disorders with the male:female ratio of 4:1, implying the contribution of X chromosome genetic factors to the susceptibility of ASD. The ribosomal protein L10 (RPL10) gene, located on chromosome Xq28, codes for a key protein in assembling large ribosomal subunit and protein synthesis. Two non-synonymous mutations of RPL10, L206M and H213Q, were identified in four boys with ASD. Moreover, functional studies of mutant RPL10 in yeast exhibited aberrant ribosomal profiles. These results provided a novel aspect of disease mechanisms for autism - aberrant processes of ribosome biosynthesis and translation. To confirm these initial findings, we re-sequenced RPL10 exons and quantified mRNA transcript level of RPL10 in our samples. Methods 141 individuals with ASD were recruited in this study. All RPL10 exons and flanking junctions were sequenced. Furthermore, mRNA transcript level of RPL10 was quantified in B lymphoblastoid cell lines (BLCL) of 48 patients and 27 controls using the method of SYBR Green quantitative PCR. Two sets of primer pairs were used to quantify the mRNA expression level of RPL10: RPL10-A and RPL10-B. Results No non-synonymous mutations were detected in our cohort. Male controls showed similar transcript level of RPL10 compared with female controls (RPL10-A, U = 81, P = 0.7; RPL10-B, U = 61.5, P = 0.2). We did not observe any significant difference in RPL10 transcript levels between cases and controls (RPL10-A, U = 531, P = 0.2; RPL10-B, U = 607.5, P = 0.7). Conclusion Our results suggest that RPL10 has no major effect on the susceptibility to ASD.